2015
DOI: 10.1186/s13643-015-0076-5
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review protocol to evaluate the psychometric properties of measures of function within adult neuro-rehabilitation

Abstract: BackgroundSpasticity in the upper limb is common after acquired brain impairment and may have a significant impact on the ability to perform meaningful daily activities. Traditionally, outcome measurement in spasticity rehabilitation has focused on impairment, however, improvements in impairments do not necessarily translate to improvements in an individual’s ability to perform activities or engage in life roles. There is an increasing need for outcome measures that capture change in activity performance and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…It has been used in many systematic reviews to evaluate studies and instruments of various diseases, such as hip and knee osteoarthritis, geriatrics, non-small cell lung carcinoma, and neuro-rehabilitation patients. 24 27 In terms of COPD, COSMIN has been used to assess COPD assessment test (CAT) questionnaire, health-related quality of life (HRQOL) questionnaires, and arm exercise capacity. 28 30 In this article, we employed COSMIN to review both patient-reported measures and performance-based measures of COPD patients’ functional status.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used in many systematic reviews to evaluate studies and instruments of various diseases, such as hip and knee osteoarthritis, geriatrics, non-small cell lung carcinoma, and neuro-rehabilitation patients. 24 27 In terms of COPD, COSMIN has been used to assess COPD assessment test (CAT) questionnaire, health-related quality of life (HRQOL) questionnaires, and arm exercise capacity. 28 30 In this article, we employed COSMIN to review both patient-reported measures and performance-based measures of COPD patients’ functional status.…”
Section: Introductionmentioning
confidence: 99%
“…In treatment for spasticity, it is important to educate patients and caregivers carefully before initiating treatment and to discuss realistic treatment goals, including how much improvement should be expected in daily life difficulties associated with spasticity, such as difficulties in dressing, pain, and decreased locomotion [1, 30]. A systematic review of neurorehabilitation outcomes after BT reported that a mechanism for capturing how benefits can be applied to daily life is needed [31]. The characteristics of the conflicts observed in our study were based on the patients’ everyday lives, including conflicts between perceptions of “BT effects that correspond to the restriction of one’s life and the emergence of an image of desired treatment” and the “fear of being unable to maintain the status quo because of the side effects of BT.” Addressing these conflicts requires thinking about how to apply treatment benefits to a patient’s daily life [31].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of neurorehabilitation outcomes after BT reported that a mechanism for capturing how benefits can be applied to daily life is needed [31]. The characteristics of the conflicts observed in our study were based on the patients’ everyday lives, including conflicts between perceptions of “BT effects that correspond to the restriction of one’s life and the emergence of an image of desired treatment” and the “fear of being unable to maintain the status quo because of the side effects of BT.” Addressing these conflicts requires thinking about how to apply treatment benefits to a patient’s daily life [31]. In response to these conflicts, healthcare professionals should take the following steps to provide support prior to treatment to enhance the development of patients’ decision-making processes: 1) verify the patient’s current condition (i.e., the lifestyle that a patient is currently able to lead); 2) provide information on risk management as well as on the benefits of the patient’s lifestyle; and 3) establish treatment strategies that maintain the positive aspects of the patient’s present lifestyle through discussions with the patient and his/her family members.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of included papers was evaluated using the COSMIN checklist with 4-point scale. This checklist was applied to determine whether each study met the standards for methodological quality with regard to internal consistency, reliability (test-retest, inter-rater and intrarater), measurement error, content validity (including face validity), structural validity, hypothesis testing, cross-cultural validity, criterion validity, responsiveness, interpretability and generalisability (Pike et al, 2015;Terwee et al, 2012). A rating of "excellent", "good", "fair" or "poor" was assigned for each measurement property.…”
Section: Discussionmentioning
confidence: 99%
“…To identify relevant articles, searches were conducted of the following from inception until December 2017: Medical Literature Analysis and Retrieval System Online (MEDLINE), Cumulative Index to Nursing and Allied Health Literature (CINAHL) and Excerpta Medica dataBASE (EMBASE). The search strategy is reported in a larger evaluation of upper limb function assessments (Pike et al ., ). Studies were included: if the original version of the ARAT was used with no modifications, in full, with all items administered and data reported; if the study was conducted and reported in English; if any of the psychometric properties defined by COSMIN were investigated; if it was an original study that collected data; if the original ARAT was either the primary outcome measure or was used in such a way that its psychometric properties were still evaluated and reported; and if reports were in peer‐reviewed literature.…”
Section: Methodsmentioning
confidence: 97%